2004
DOI: 10.1111/j.1600-0854.2004.00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Annexin–Actin Interactions

Abstract: The actin cytoskeleton is a malleable framework of polymerised actin monomers that may be rapidly restructured to enable diverse cellular activities such as motility, endocytosis and cytokinesis. The regulation of actin dynamics involves the coordinated activity of numerous proteins, among which members of the annexin family of Ca 2+ -and phospholipid-binding proteins play an important role. Although the roles of annexins in actin dynamics are not understood at a mechanistic level, annexins have the requisite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
189
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(195 citation statements)
references
References 50 publications
5
189
0
1
Order By: Relevance
“…Their highly conserved so-called "core" module bears the unique Ca 2ϩ -binding sites that mediate a Ca 2ϩ -dependent, reversible binding to cellular membranes (Gerke et al, 2005). Some annexins also interact with F-actin filaments and certain phosphatidylinositides such as phosphatidylinositol (4,5)-bisphosphate [PtdIns(4,5)P 2 ] (Hayes et al, 2004;Rescher and Gerke, 2004). Due to their properties, they might form membrane scaffolds that organize and/or stabilize certain membrane domains and in some cases link them to the underlying actin cytoskeleton (for review, see Hayes et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their highly conserved so-called "core" module bears the unique Ca 2ϩ -binding sites that mediate a Ca 2ϩ -dependent, reversible binding to cellular membranes (Gerke et al, 2005). Some annexins also interact with F-actin filaments and certain phosphatidylinositides such as phosphatidylinositol (4,5)-bisphosphate [PtdIns(4,5)P 2 ] (Hayes et al, 2004;Rescher and Gerke, 2004). Due to their properties, they might form membrane scaffolds that organize and/or stabilize certain membrane domains and in some cases link them to the underlying actin cytoskeleton (for review, see Hayes et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Some annexins also interact with F-actin filaments and certain phosphatidylinositides such as phosphatidylinositol (4,5)-bisphosphate [PtdIns(4,5)P 2 ] (Hayes et al, 2004;Rescher and Gerke, 2004). Due to their properties, they might form membrane scaffolds that organize and/or stabilize certain membrane domains and in some cases link them to the underlying actin cytoskeleton (for review, see Hayes et al, 2004). Recent studies demonstrated that annexin A2 and annexin A1 function in the endocytic pathway (Mayran et al, 2003;Zobiack et al, 2003;White et al, 2006), although their precise mechanism of action is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Since previously we observed a profound stimulatory effect of GTE on actin polymerization, 14 we hypothesized that GTE-induced actin remodeling might be associated with annexin-I upregulation. To test this hypothesis, we first analyzed the association of annexin-I expression and F-actin using triple-labeling immunofluorescence.…”
Section: Gte-induced Annexin-i Expression Correlated With Actin Polymmentioning
confidence: 99%
“…Generally, Annexin II has been shown to be involved in the regulation of membrane organization (i.e. stabilization of lipid rafts), membrane-cytoskeleton linkage, membrane trafficking, and endocytosis [22]. These functions of Annexin II are related to its Ca 2+ -dependent binding of the protein to phospholipids [23].…”
Section: Discussionmentioning
confidence: 99%